MENGANALISIS HUBUNGAN PROKRASTINASI AKADEMIK TERHADAP PRESTASI BELAJAR MAHASISWA - Bani , Maria Francisce; Taek, Emilia Dolorosa; Ngongo, Maria Hendritha Lidya (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2022)
The purpose of this study was to find out the description of academic procrastination on student achievement for class of 2020 for the 2022/2023 academic year STIPAS Archdiocese of Kupang, to find out the relationship between academic procrastination on student achievement for class 2020 for the 2022/2023 academic year STIPAS Archdiocese of Kupang. This study used a descriptive quantitative method with research locations at STIPAS, Kupang Archdiocese. The population in this study were 78 people consisting of 38 students in class A and 40 students in class B and the sample used was the same as the population. The data collection technique used in this research is. While the data analysis techniques in this study are descriptive data analysis and inferential data analysis techniques. The results of the research based on statistical analysis show that the relationship between academic procrastination and student achievement in class 2020 at STIPAS Archdiocese of Kupang is 68.2%, meaning that academic procrastination has a significant relationship to learning achievement. Based on the results of the hypothesis testing it was found that the significance value was 0.00 with a probability of 0.05, so the decision was to reject the hypothesis (Ho) and accept the hypothesis (Ha) meaning that the academic procrastination variable has a significant relationship to learning achievement.